Energy-Reduced Fabrication of Light-Frame Ceramic Honeycombs by Replication of Additive Manufactured Templates - Köllner, David; Niedermeyer, Sebastian; Vermes, Miklos; Simon, Swantje; Kakimoto, Ken Ichi; Fey, Tobias (Materials, 2023)
Ceramic components require very high energy consumption due to synthesis, shaping, and thermal treatment. However, this study suggests that combining the sol–gel process, replica technology, and stereolithography has the potential to produce highly complex geometries with energy savings in each process step. We fabricated light-frame honeycombs of Al2O3, Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT), and BaTiO3 (BT) using 3D-printed templates with varying structural angles between −30° and 30° and investigated their mechanical and piezoelectric properties. The Al2O3 honeycombs showed a maximum strength of approximately 6 MPa, while the BCZT and BaTiO3 honeycombs achieved a d33 above 180 pC/N. Additionally, the BCZT powder was prepared via a sol–gel process, and the impact of the calcination temperature on phase purity was analyzed. The results suggest that there is a large energy-saving potential for the synthesis of BCZT powder. Overall, this study provides valuable insights into the fabrication of complex ceramic structures with improved energy efficiency and enhancement of performance.
CRIS-Team Scopus Importer:2023-08-11
Keywords: additive manufacturing; ceramic honeycombs; piezoelectric porous ceramics; replica method; sol–gel method